2011
DOI: 10.5194/acp-11-11055-2011
|View full text |Cite
|
Sign up to set email alerts
|

Volatility of secondary organic aerosol during OH radical induced ageing

Abstract: Abstract. The aim of this study was to investigate oxidation of SOA formed from ozonolysis of α-pinene and limonene by hydroxyl radicals. This paper focuses on changes of particle volatility, using a Volatility Tandem DMA (VTDMA) set-up, in order to explain and elucidate the mechanism behind atmospheric ageing of the organic aerosol. The experiments were conducted at the AIDA chamber facility of Karlsruhe Institute of Technology (KIT) in Karlsruhe and at the SAPHIR chamber of Forchungzentrum Jülich (FZJ) in Jü… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 50 publications
13
82
0
Order By: Relevance
“…We observed cloud condensation nucleus (CCN) activity (39), volatility via tandem differential mobility analysis (V-TDMA) (12,13), and subsaturated water uptake via hygroscopicity TDMA (H-TDMA) (12). The CCN activity of the organics was largely unaffected by either ripening or OH oxidation (39).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We observed cloud condensation nucleus (CCN) activity (39), volatility via tandem differential mobility analysis (V-TDMA) (12,13), and subsaturated water uptake via hygroscopicity TDMA (H-TDMA) (12). The CCN activity of the organics was largely unaffected by either ripening or OH oxidation (39).…”
Section: Resultsmentioning
confidence: 96%
“…Volatility (Fig. 3B) showed a consistent temporal pattern in AIDA, PSI, and SAPHIR, responding to ripening and to OH aging (12,13). Volatility measured by the volume fraction remaining at a fixed elevated temperature decreased progressively during ripening, increased sharply with the introduction of OH, and then reverted to a more gradual progressive decrease after roughly 1 h of OH aging.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, Cappa and Jimenez (2010) found that a large portion of the ambient OA mass in Mexico City was nonvolatile, while Lee et al (2010) discovered that most OA in a remote region near Finokalia in Crete, Greece, was semi-volatile. In chamber studies, Salo et al (2011) found that aerosol ageing took place in the gas phase due to OH oxidation of semi-volatile organic compounds and intermediate-volatility organic compounds rather than by bulk or surface reactions. Furthermore, the effects of particle volatility on CCN number and activity have also been investigated.…”
Section: Introductionmentioning
confidence: 99%